Electrical Discharge Machine (EDM): evaluasi nilai kekasaran permukaan benda kerja pengaruh variasi kuat arus listrik dan kekerasan material - Eko Budiyanto; Eko Nugroho; YGK Putra (Universitas Muhammadiyah Metro, 2020)
Electrical Discharge Machine (EDM) is a manufacturing machine that can be used to make workpieces with complicated shapes that cannot be worked on conventional machines. The main process of EDM is to erode the workpiece in the plasma zone that is formed as a result of an electric current that flows and jumps of sparks that occur between the electrodes. Some factors that affect the success of the EDM process include the strong electric current and mechanical properties of the workpiece. The use of EDM in steel material for its processing includes various grades of hardness. This study aims to evaluate the value of the roughness of the workpiece EDM process results that are affected by strong electric current and material hardness. This study uses EDM King Spark ZNC ADM-PM Series and steel material as workpieces. The independent variables used in this study were 3 levels of current use namely 6 Amperes, 9 Amperes & 12 Amperes, and 3 levels of steel hardness namely 28.2 HRC, 31.7 HRC & 37.9 HRC with 18 specimens. Data retrieval is carried out in 3 stages, namely data retrieval of material hardness, retrieval of material composition test data, and retrieval of surface roughness test data. The results showed that the higher the current value and the hardness of the steel used will increase the value of surface roughness. The best surface roughness value of each specimen examined is specimen A with a steel hardness of 31.7 HRC and a current value of 6 Amperes resulting in surface roughness of 3.07 μm; in specimen B with a steel hardness of 28.2 HRC and a current value of 6 Amperes resulting in a surface roughness value of 2.66 μm; and in specimen C with a steel hardness of 37.9 HRC and a current value of 9 Amperes resulting in a surface roughness value of 2.92 μm.Keywords: EDM, electric current, violence, roughness, and steel.